TRYPANORHYNCHID CESTODES FROM FISHES OF KHOR –ABDULLAH, ARABIAN GULF - Majid A.A.Bannai (Basrah Journal of Veterinary Research)
Results of the present investigation on infection of Trypanorhychid cestode infestation of marine fishes of Khor –Abdulla North west Arabian Gulf throws June 2006 to May 2007 . revealed to presence of four different species Trypanorhychid cestodes:-. :Callitrahynchus gracilis , Dasyrhynchus pacificus from Scomberoides cammmersoniaus ; Nybelinia lamonteae from Saurida undosquamis ; Otobothrium penetratus from Synaptura orientalis ;Pterobthrium hira from Illisha elongata. which all represented as a new locality recorded parasite